Intra-coronary physiology in contemporary percutaneous coronary intervention and anginal therapy with a focus on microvascular disease - Alisiddiq, Zaheer; Sharma, Harish; Cotton, James; Fan, Lampson (Frontiers in Cardiovascular Medicine, 2023)
Coronary physiological measurements have transformed the treatment of coronary artery disease (CAD), with increasing evidence supporting the use of pressure wire guided revascularisation. Advances in microvascular assessment have enabled clinicians to discern angina aetiology even in patients without obstructive epicardial coronary artery disease, paving the way for more effective tailored therapy. In this article, the authors will examine pressure wire indices, their role in influencing clinical outcomes and future directions.